2017
DOI: 10.1002/joc.5236
|View full text |Cite
|
Sign up to set email alerts
|

Key features of cold‐air pool episodes in the northeast of the Iberian Peninsula (Cerdanya, eastern Pyrenees)

Abstract: The aim of this research was to detect cold‐air pool (CAP) days during winter and quantify the synoptic situations that produce decoupling between free air and valley bottom temperatures in the Cerdanya basin in the eastern Pyrenees (Spain). Patterns prone to CAP (see figure) are defined by an anticyclonic ridge over the Iberian Peninsula and absence of surface wind in Cerdanya, especially in December and January. Warm air advection from the south is also associated with some of the patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 47 publications
(69 reference statements)
3
21
0
1
Order By: Relevance
“…surrounding landscape and the whole domain. Nocturnal temperature inversions depends on terrain morphology, which determines where cool pools are formed (Miró et al, 2010;Miró et al, 2017).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…surrounding landscape and the whole domain. Nocturnal temperature inversions depends on terrain morphology, which determines where cool pools are formed (Miró et al, 2010;Miró et al, 2017).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…The most widely used spatio‐temporal fixed air temperature lapse rate is the mean environmental lapse rate (MELR: −6.5 °C/km); this parameter was presented by Barry and Chorley () as a global lapse rate calculated for the free atmosphere air temperature, and not for near‐surface air temperature. However, caution is required in use of the MELR because of the spatio‐temporal variability of near‐surface air temperature lapse rates (Pepin et al, ; ; Rolland, ; Lundquist and Cayan, ; Blandford et al, ; Minder et al, ; Dumas, ; Kattel et al, ; Miró et al, ), especially in areas covered by ice or snow (Braun and Hock, ). This is because the fixed MELR assumes no changes among seasons, synoptic conditions, or topographic complexity (Barry, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported significant temporal variability in NSLR at daily and seasonal scales in various mountain regions including the Rocky (Kunkel, 1989;Pepin and Losleben, 2002;Blandford et al, 2008) and Appalachian (Bolstad et al, 1998) mountains in the United States, in China (Fang and Yoda, 1988;Tang and Fang, 2006;Du et al, 2010), the Himalayan mountains (Kattel et al, 2013;Immerzeel et al, 2014), the Alps (Rolland, 2003;Dumas, 2013;Kirchner et al, 2013;Nigrelli et al, 2017), and polar areas (Marshall et al, 2007). These studies have reported steeper NSLRs under unstable atmospheric conditions, and marked differences in NSLR have been found as a function of synoptic conditions (Pepin et al, 1999;Pepin, 2001;Blandford et al, 2008;Holden and Rose, 2011;Kirchner et al, 2013;Miró et al, 2018). These findings indicate that these effects need to be taken into account when analysing the temporal and spatial evolution of the NSLR.…”
mentioning
confidence: 96%
“…It is a singular basin due to its orographic configuration which predisposes the formation of cold air pools, mountain gravity waves and enhanced precipitation (Trapero et al, 2013, Miró et al, 2018.…”
Section: 5mentioning
confidence: 99%